IMPLEMENTING EXPERIENTIAL LEARNING METHOD TO ENHANCE STUDENTS’ SPEAKING SKILL - Naulan Millatina; Sofyan A. Gani; Iskandar Abdul Samad (English Education Journal, 2020)
Foreign language students may face difficulties in developing speaking skills due to the reasons of lacking the opportunity to speak, the inhibition or enxity, and lacking the motivation to study. This study aimed to investigate the implementation of Experiential Learning Method as an effort to solve such problems. Thus, there were two objectives in this study which were to examine the difference of speaking achievement on the use of Experiential Learning Method and to find out the students’ responses toward the method. The sample was taken by using random sampling from the population of the first grade students at SMAN1 Banda Aceh in the 2019/2020 academic year. Two classes were taken as the sample, each for experimental class and control class. The data were analyzed by using t-test through SPSS for speaking test and percentage for questionnaire. The result showed that Experiential Learning Method was more effective than conventional method (teacher centred) to teach speaking. Also, the students had a quite positive response to the use of Experiential Learning Method in their speaking class. It can be concluded that the Experiential Learning Method provides a positive contribution for the development of the students’ speaking performance.